An APPLICATION OF GONADOTROPIN HORMONES ON ARTIFICIAL SPAWNING SANGKURIANG CATFISH (Clarias sp.) - Indra Kristiana; Erna Fitriani; Muhammad Akbarurasyid; Wahyu Puji Astiyani; Atiek Pietoyo (Universitas Mataram, 2024)
The demand for catfish increases every year, the production that occurs is not yet able to handle market demand. To meet the demand optimally, artificial spawning is carried out using gonadotropin hormones at different doses. This research aims to determine the right use of dosage in the artificial spawning process of sangkuriang catfish based on fecundity, FR, HR and SR. This research was carried out using 3 doses, namely for treatment P (0.1 ml/kg), Q (0.2 ml/kg) and R (0.3 ml/kg), each treatment was carried out in 3 repetitions. The results showed that the administration of gonadotropins achieved the highest fertility level in in spawning with a gonadotropin dose of 0.3 ml/kg of 62,150 grains. Meanwhile, the lowest fecundity value occurred in spawning with a gonadotropin dose of 0.1 ml/kg of 46,240 grains. The highest FR value was obtained when using a gonadotropin dose of 0.1 ml/kg which resulted in the highest FR value of 98.36% and the lowest FR using a gonadotropin dose of 0.3 ml/kg of 87.85%. The highest HR value was obtained at a dose of 0.1 ml/kg of 94.20%, and the lowest HR value at a dose of 0.2 ml/kg of 68.5%. The highest SR value was obtained at a dose of 0.1 ml/kg at 94.61% and the lowest SR value at a dose of 0.2 ml/kg of 54.39%. Based on the FR value at a dose of 0.1 ml/kg of 98.36%, for the HR value at a dose of 0.1 ml/kg of 94.61%. The results of the observations concluded that the use of gonadotropins with the highest fecundity value was obtained at a dose of 0.3 ml/kg with a total of 62,150 grains. The good dose of FR, HR and SR values for artificial spawning of sangkuriang catfish with gonadotropin hormone were found at a dose of 0.1 ml/kg where the fertilization rate (FR) value is 98.36%, Hatching rate (HR) is 94.2% and survival rate (SR) is 94.61%. The value of FR, HR and SR is influenced by environmental conditions and the care carried out. Because the condition of the larvae is still very vulnerable, the immunity is still weak, rudimentary organs are still in their infancy.